Nitric Oxide Mediates Biofilm Formation and Symbiosis in Silicibacter sp. Strain TrichCH4B - Minxi Rao (American Society for Microbiology, 2015)
ABSTRACT Nitric oxide (NO) plays an important signaling role in all domains of life. Many bacteria contain a heme-nitric oxide/oxygen binding (H-NOX) protein that selectively binds NO. These H-NOX proteins often act as sensors that regulate histidine kinase (HK) activity, forming part of a bacterial two-component signaling system that also involves one or more response regulators. In several organisms, NO binding to the H-NOX protein governs bacterial biofilm formation; however, the source of NO exposure for these bacteria is unknown. In mammals, NO is generated by the enzyme nitric oxide synthase (NOS) and signals through binding the H-NOX domain of soluble guanylate cyclase. Recently, several bacterial NOS proteins have also been reported, but the corresponding bacteria do not also encode an H-NOX protein. Here, we report the first characterization of a bacterium that encodes both a NOS and H-NOX, thus resembling the mammalian system capable of both synthesizing and sensing NO. We characterized the NO signaling pathway of the marine alphaproteobacterium Silicibacter sp. strain TrichCH4B, determining that the NOS is activated by an algal symbiont, Trichodesmium erythraeum. NO signaling through a histidine kinase-response regulator two-component signaling pathway results in increased concentrations of cyclic diguanosine monophosphate, a key bacterial second messenger molecule that controls cellular adhesion and biofilm formation. Silicibacter sp. TrichCH4B biofilm formation, activated by T. erythraeum, may be an important mechanism for symbiosis between the two organisms, revealing that NO plays a previously unknown key role in bacterial communication and symbiosis. IMPORTANCE Bacterial nitric oxide (NO) signaling via heme-nitric oxide/oxygen binding (H-NOX) proteins regulates biofilm formation, playing an important role in protecting bacteria from oxidative stress and other environmental stresses. Biofilms are also an important part of symbiosis, allowing the organism to remain in a nutrient-rich environment. In this study, we show that in Silicibacter sp. strain TrichCH4B, NO mediates symbiosis with the alga Trichodesmium erythraeum, a major marine diazotroph. In addition, Silicibacter sp. TrichCH4B is the first characterized bacteria to harbor both the NOS and H-NOX proteins, making it uniquely capable of both synthesizing and sensing NO, analogous to mammalian NO signaling. Our study expands current understanding of the role of NO in bacterial signaling, providing a novel role for NO in bacterial communication and symbiosis.